The Effect of Digital Infrastructure Development on Regional Economic Growth in Indonesia: A Spatial Econometrics Approach - M Gelar Faisal; Nurlaila Syarfiah Asfo; Reni Reni; Feby Arma Putra; M Andika Hariz Hamdallah (PT Mattawang Mediatama Solution, 2025)
This study examines how digital infrastructure development influences regional economic growth in Indonesia by explicitly accounting for spatial interdependence among provinces. Using a balanced panel of 34 provinces over 2015–2021 (238 observations), digital infrastructure is proxied by the proportion of individuals using the internet, while economic growth is measured as real GRDP per capita growth. Global Moran’s I indicates spatial clustering in both growth and digital connectivity, motivating a spatial econometric framework. The main specification estimates a Spatial Durbin Model (SDM) with province and year fixed effects and a row-standardized k-nearest neighbors spatial weights matrix (k=5) to capture outcome dependence and covariate spillovers. Results show that digital infrastructure has a positive and statistically significant direct effect on provincial growth, and it also produces a positive indirect effect, implying measurable spillovers to neighboring provinces. Decomposition into direct, indirect, and total impacts reveals that accounting for spatial feedback increases the estimated overall contribution of digital infrastructure relative to non-spatial interpretations. Robustness checks using alternative neighborhood definitions and alternative digital access proxies confirm the stability of the main findings, while a lagged specification suggests the relationship is not driven solely by contemporaneous reverse causality. The evidence implies that digital infrastructure is a network-type investment whose returns extend beyond administrative borders. Policy efforts should therefore combine connectivity expansion with coordinated regional planning and complementary measures—such as digital skills and MSME adoption support—to maximize growth benefits and reduce interregional digital gaps. These insights contribute to spatial growth literature by documenting Indonesia’s digital spillovers during adoption.Keywords: Digital Infrastructure, Regional Economic Growth, Spatial Econometrics, Spatial Durbin Model (SDM), Spatial Spillover Effects.